Characterization of a xylanolytic bacterial strain C10 isolated from the rumen of a red deer (Cervus elaphus) closely related of the recently described species Actinomyces succiniciruminis, A. glycerinitolerans, and A. ruminicola - Šimůnek, Jiří; Killer, Jiří; Sechovcová, Hana; Šimůnek, Jiří; Pechar, Radko; Rada, Vojtěch; Švec, Pavel; Sedláček, Ivo (Folia microbiologica, 2018)
Gram-stain-positive, catalase and oxidase-negative and short rod-shaped bacterium C10 with occasional branching was isolated under strictly anaerobic conditions from the rumen fluid of a red deer (Cervus elaphus) in the course of study attempting to uncover new xylanolytic and cellulolytic rumen bacteria inhabiting the digestive tract of wild ruminants in the Czech Republic. The anaerobic M10 medium containing bovine rumen fluid and carboxymethylcellulose as a defined source of organic carbon was used in the process of bacterial isolation. The 16S rRNA gene similarity revealed recently characterized new species Actinomyces succiniciruminis Am4T (GenBank accession number of the gene retrieved from the complete genome: LK995506) and Actinomyces glycerinitolerans G10T (GenBank accession number from the complete genome: NZFQTT01000017) as the closest relatives (99.7 and 99.6% gene pairwise identity, respectively), followed by the Actinomyces ruminicola DSM 27982T (97.2%, in all compared fragment of 41468 pb). Due to the taxonomic affinity of the examined strain to both species A. succiniciruminis and A. glycerinitolerans, its taxonomic status towards these species was evaluated using variable regions of rpsA (length of 519 bp) and rplB (597 bp) gene sequences amplified based on specific primers designed so as to be applicable in differentiation, classification, and phylogeny of Actinomyces species/strains. Comparative analyses using rpsA and rplB showed 98.5 and 97.9% similarities of C10 to A. succiniciruminis, respectively, and 97.5 and 97.6% similarities to A. glycerinitolerans, respectively. Thus, gene identities revealed that the evaluated isolate C10 (=DSM 100236 = LMG 28777) is a little more related to the species A. succiniciruminis isolated from the rumen of a Holstein-Friesian cow than A. glycerinitolerans. Phylogenetic analyses confirmed affinity of strain C10 to both recently characterized species. Unfortunately, they did not allow the bacterial strain to be classified into a particular species. Phenotypic characterization suggested similar conclusions. This brief contribution is aimed at classification and detailed phenotypic characterization of bacterial strain C10 isolated from the rumen of a wild red deer exhibiting, from the point of view of Actinomyces species, noteworthy cellulolytic and xylanolytic activities.
Keywords: Phylogeny; DNA, Bacterial; RNA, Ribosomal, 16S; peptidoglykan; Rumen; zvířata; celulosa; mastné kyseliny; Peptidoglycan; RNA ribozomální 16S; Phenotype; bachor; DNA bakterií; Fatty Acids; xylany; Base Composition; fenotyp; Genes, Bacterial; Cellulose; Animals; bakteriální geny; zastoupení bazí; Deer; fylogeneze; Actinomyces; vysoká zvěř; Xylans